Practice the Technique of Singing Vietnamese Light Music Song for Middle-age Female Voices - Lam, Do Thi (International Journal of Humanities and Education Development (IJHED), 2024)
Classical chamber music vocal techniques, typically the bel canto singing style, have been shaped with many methodical methods. In our country, several famous vocal pedagogues have compiled and written books on teaching vocal music such as Nguyen Trung Kien and Ho Mo La. Unlike classical chamber singing, currently, in our country, there are no books or unified in-depth research on light music singing techniques. While classical vocal techniques require strictness and the singer must accurately perform every detail recorded in the song, light music is characterized by a fairly free and comfortable way of singing from the mouth, how to vibrate your voice, process sound to express your work... Singers can be creative from their point of view, as long as they create their mark and attract listeners.